2017
DOI: 10.1590/s0102-053620170321
|View full text |Cite
|
Sign up to set email alerts
|

Performance of advanced potato clones: plant vigor, tuber yield and specific gravity

Abstract: The aim of this work was to evaluate the performance of advanced potato clones for plant vigor, tuber yield components and specific gravity. Two sets of advanced clones and two control cultivars broadly grown in Brazil were compared. The first set, formed by 11 clones, was evaluated in the spring season of 2010, and the second, constituted by six clones, in the autumn season of 2011, in Canoinhas, Santa Catarina State, Brazil. The design of both experiments was a randomized complete block with four replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…According to Silva et al (2018b), traits related to the plant vegetative growth, such as stem number, stem size and plant vigor are related to the index of vegetative area available for photosynthesis. Some studies reported direct relationship of these traits with tuber yield, such as the positive relationship between plant height and tuber yield (Khayatnezhad et al, 2011;Arslan, 2007;Fekadu et al, 2013), and plant vigor with tuber yield (Silva et al, 2007;Pereira et al, 2017).…”
Section: Brasilia Experimentsmentioning
confidence: 99%
“…According to Silva et al (2018b), traits related to the plant vegetative growth, such as stem number, stem size and plant vigor are related to the index of vegetative area available for photosynthesis. Some studies reported direct relationship of these traits with tuber yield, such as the positive relationship between plant height and tuber yield (Khayatnezhad et al, 2011;Arslan, 2007;Fekadu et al, 2013), and plant vigor with tuber yield (Silva et al, 2007;Pereira et al, 2017).…”
Section: Brasilia Experimentsmentioning
confidence: 99%
“…These two varieties, together with AR 08 had good plant vigour, reflected in their plant size (assessed from plant height and stem diameter). Plant vigour is an important property, considering that vigorous plant correlates positively with tuber yield [12].…”
Section: Resultsmentioning
confidence: 99%
“…Variation in plant vigor among the genotypes is attributed to both genotype and environmental factors [19,20]. Plant vigor is influenced by nutrient uptake and utilization by the different genotypes.…”
Section: Discussionmentioning
confidence: 99%